2020
DOI: 10.1093/ibd/izaa075
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Signatures That Define Ulcerative Colitis in Remission

Abstract: Background This study addresses whether existing specific transcriptional profiles can improve and support the current status of the definition of ulcerative colitis (UC) remission apart from the existing endoscopic, histologic, and laboratory scoring systems. For that purpose, a well-stratified UC patient population in remission was compared to active UC and control patients and was investigated by applying the next-generation technology RNA-Seq. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 63 publications
1
33
0
2
Order By: Relevance
“…10 In addition, recent gene expression studies have shown the presence of a continuous inflammatory-like state and a gene dysregulation in colonic biopsy specimens from patients with quiescent UC. [11][12][13] The immunomodulating determinants involved in the education of intestinal macrophages still are not fully defined, but intestinal microbiota and microbiota-derived metabolites increasingly are recognized for their role in imprinting tissue-specific features of intestinal macrophages. 5,14 In addition to this, it is known that UC patients show a dysbiotic microbiota composition, including a decrease in Firmicutes and Bacteroidetes phyla 15,16 and altered fecal metabolite profiles, 17 which could affect intestinal macrophage maturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, recent gene expression studies have shown the presence of a continuous inflammatory-like state and a gene dysregulation in colonic biopsy specimens from patients with quiescent UC. [11][12][13] The immunomodulating determinants involved in the education of intestinal macrophages still are not fully defined, but intestinal microbiota and microbiota-derived metabolites increasingly are recognized for their role in imprinting tissue-specific features of intestinal macrophages. 5,14 In addition to this, it is known that UC patients show a dysbiotic microbiota composition, including a decrease in Firmicutes and Bacteroidetes phyla 15,16 and altered fecal metabolite profiles, 17 which could affect intestinal macrophage maturation.…”
mentioning
confidence: 99%
“… 10 In addition, recent gene expression studies have shown the presence of a continuous inflammatory-like state and a gene dysregulation in colonic biopsy specimens from patients with quiescent UC. 11 , 12 , 13 …”
mentioning
confidence: 99%
“…To test whether a similar phenomenon may occur in IBD patients, we investigated IBD transcriptomic datasets. For this, we analyzed two publicly available IBD transcriptomic datasets: (a) the treatment of a naïve pediatric ulcerative colitis cohort (PROTECT [ 32 ]), representing patients from both sexes with active UC as well as control patients without active ulcerative colitis; and (b) a dataset representing adult active UC and UC in remission and controls (Fenton et al cohort) [ 33 ]. Interestingly, consistent with our observations on the experimental colitis, UC patients also showed an increased expression in the genes for neuroglia ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…We used previously published transcriptomic datasets from PROTECT [ 32 ] (accession: GSE109142, 206 samples from ulcerative colitis, and 20 samples from non-inflamed rectum tissues) and Fenton et al [ 33 ] (accession: GSE128682, 16 control samples from normal colon tissues, 14 samples from active ulcerative colitis colon tissues, and 14 samples from colon tissues from ulcerative colitis patients in remission) cohorts. The gene expression changes in the neuroglial identifiers established in our study were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Datasets. The gene expression data were collected from the Gene Expression Omnibus (GEO) database with accession GSE128682, and the sample collection was described in an earlier study [14]. The counts for each sample were normalized by DESeq2 [15].…”
Section: Methodsmentioning
confidence: 99%